The twisted claw - Dixon, Franklin W. (New York Grosset & Dunlap, 1969)
The Hardy boys embark on another puzzling mystery when they try to discover who is stealing rare collections of ancient pirate treasure and smuggling them out of the United States.
Keywords: Detective and mystery stories -- Juvenile fiction